2020
DOI: 10.1186/s12889-020-09843-7
|View full text |Cite
|
Sign up to set email alerts
|

A modelling study highlights the power of detecting and isolating asymptomatic or very mildly affected individuals for COVID-19 epidemic management

Abstract: Background Mathematical modelling of infectious diseases is a powerful tool for the design of management policies and a fundamental part of the arsenal currently deployed to deal with the COVID-19 pandemic. Methods We present a compartmental model for the disease where symptomatic and asymptomatic individuals move separately. We introduced healthcare burden parameters allowing to infer possible containment and suppression strategies. In addition, the model was scaled up to describe different interconnected ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…During Chicago's October 2020 epidemic wave, mitigation was implemented on November 20[31] when the COVID-19 ICU occupancy was 53% (S1Fig 16). However, Rt had already begin to decrease prior to implementation of official mitigation measures as individual action preceded government policy (S1Fig 17).Our suggested threshold of 60% for Chicago aligns with thresholds used in a modeling study that simulated multiple on-off cycles based on a fixed 50% ICU occupancy threshold[26]. Another modeling study evaluated an ICU threshold system that defined 30% occupancy as moderate risk, 30-60% occupancy as higher risk, and above 60% as very high risk[18].…”
supporting
confidence: 56%
See 2 more Smart Citations
“…During Chicago's October 2020 epidemic wave, mitigation was implemented on November 20[31] when the COVID-19 ICU occupancy was 53% (S1Fig 16). However, Rt had already begin to decrease prior to implementation of official mitigation measures as individual action preceded government policy (S1Fig 17).Our suggested threshold of 60% for Chicago aligns with thresholds used in a modeling study that simulated multiple on-off cycles based on a fixed 50% ICU occupancy threshold[26]. Another modeling study evaluated an ICU threshold system that defined 30% occupancy as moderate risk, 30-60% occupancy as higher risk, and above 60% as very high risk[18].…”
supporting
confidence: 56%
“…Our suggested threshold of 60% for Chicago aligns with thresholds used in a modeling study that simulated multiple on-off cycles based on a fixed 50% ICU occupancy threshold [26]. Another modeling study evaluated an ICU threshold system that defined 30% occupancy as moderate risk, 30-60% occupancy as higher risk, and above 60% as very high risk [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One model estimated that transmission from asymptomatic individuals accounts for over half of all covid-19 transmissions, after considering scenarios with multiple covid-19 infectious periods and varying rates of transmission from those who never displayed symptoms 15. Several prediction models have indicated that the identification and isolation of all infected individuals, including those who are asymptomatic, is important for controlling the spread of covid-19 161718. In a worst scenario of unmitigated growth, researchers estimated that testing asymptomatic people may identify the virus five to eight days earlier than it would be detected in symptomatic people, a significant difference.…”
Section: Importance Of Control and Preventionmentioning
confidence: 99%
“…Isolation is an indispensable measure to contain the SARS-CoV-2 virus and affects millions of people worldwide [ 1 , 2 ]. However, isolation, even if short-term, may also have a negative impact.…”
Section: Introductionmentioning
confidence: 99%